Come Die with Me: A Riddle in ’King Lear’ - Stella, Massimo (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2021)
This article explores a case of methodological criticism that has been neglected by Shakespearean scholars and, amongst them, philologists and critics who have studied and edited King Lear: namely, the mythic and linguistic model of Shakespeare’s King Lear between Freud (The Theme of the Three Caskets) and Lévi-Strauss (The Structural Study of Myth), in the re-reading of the eminent French classicist Clémence Ramnoux.